Strategic planning and territorial cohesion in Morocco: construction of a cohesion index and lessons for regional planning - KERDAD , Ouail; EL HANI , Zahira (Revue Internationale des Sciences de Gestion, 2025)
One of the most important components of balanced and sustainable land use planning is the coordination between strategic planning and territorial cohesion. In Morocco, although developing rapidly, the advanced regionalization framework is failing to quickly reduce socioeconomic disparities between regions. This article aims to examine in depth how strategic planning policies are linked to territorial cohesion using a mixed-method approach, including qualitative interviews with institutional informants and a quantitative analysis of regional indicators and the mathematical treatment of the territorial cohesion index. The results suggest that although current policies aimed at reducing regional inequalities are ambitious, they lack territorial integration or articulation between national projects and local realities. Finally, the authors recommend the creation of a National Territorial Cohesion Index that measures accessibility, equity of services, and economic performance of regions to make land use plans more relevant and effective in the future.